Integration of Sukoharjo Local Wisdom in The Encyclopedia Digital Ethnoscience for Science Learning In Elementary Schools - Sari, Nurratri Kurnia; Sukarno, Sukarno; Adriyanto, Adriyanto; Wicaksana, Muhlis Fajar; Pardyatmoko, Pardyatmoko (Jurnal Mamangan, 2023)
Natural Science (IPA) learning today in elementary schools tends to be still theoretical and less contextual with students' lives. This research aims to develop science teaching materials in the form of an ethnoscience-based digital encyclopedia that integrates the local wisdom of Sukoharjo Regency. The ethnoscience approach is used to bridge scientific concepts with local cultural values to increase the relevance and meaning of learning. The method used is Research and Development (R&D) with the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. Data were obtained through literature studies, field observations, interviews with community leaders, and validation by material and media experts. Preliminary results suggest that various local practices, such as traditional food processing, herbal medicine, and agricultural systems, have scientific value that can be integrated into science material. The developed digital encyclopedia is equipped with illustrations, interactive narratives, and multimedia content to make it easier for students to understand. These findings show that the development of ethnoscience-based contextual teaching materials has the potential to improve the quality of science learning in elementary schools in a creative, meaningful, and rooted in local culture